2008
DOI: 10.1016/j.ophtha.2008.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Combining Nerve Fiber Layer Parameters to Optimize Glaucoma Diagnosis with Optical Coherence Tomography

Abstract: Purpose-To identify the best combination of Stratus optical coherence tomography (OCT) retinal nerve fiber layer (RNFL) thickness parameters for the detection of glaucoma. Design-Observational cross-sectional study.Participants-Eighty-nine age-matched normal and perimetric glaucoma participants enrolled in the Advanced Imaging for Glaucoma Study.Methods-The Zeiss Stratus OCT system was used to obtain the circumpapillary RNFL thickness in both eyes of each participant. Right and left eye clock-hour data are ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 41 publications
(60 reference statements)
1
70
0
1
Order By: Relevance
“…8 Table 4 shows a summary of publications on RNFL thickness evaluation in normal patients using the OCT. [9][10][11][12][13][14][15][16][17][18][19] The table is restricted to studies using 3.4-mm diameter OCT circle scans and to study populations containing predominantly white patients to be able to compare the results with ours (adjusted to mean age, age range, and range of refractive error if information available in the respective publication). The RNFL thickness measured with SOCT in our study was very close to the reported RNFL thicknesses measured with Stratus OCT in most reports, especially in the more recent ones.…”
Section: Discussionmentioning
confidence: 99%
“…8 Table 4 shows a summary of publications on RNFL thickness evaluation in normal patients using the OCT. [9][10][11][12][13][14][15][16][17][18][19] The table is restricted to studies using 3.4-mm diameter OCT circle scans and to study populations containing predominantly white patients to be able to compare the results with ours (adjusted to mean age, age range, and range of refractive error if information available in the respective publication). The RNFL thickness measured with SOCT in our study was very close to the reported RNFL thicknesses measured with Stratus OCT in most reports, especially in the more recent ones.…”
Section: Discussionmentioning
confidence: 99%
“…The AUROC values were computed as in previous studies. 9,33,34 The AUROCs of Mahalanobis distances were also calculated. In addition, for each evaluated parameter, sensitivity and specificity were assessed according to the formula mean þ 2.33 standard deviations for the normal group, and the first percentile value FIGURE 2.…”
Section: Methodsmentioning
confidence: 99%
“…Optical coherence tomography (OCT), first described in 1991 by Huang et al, 1 has a major role in this context and has been applied in the diagnosis of several diseases of the optic nerve, such as glaucoma, optic neuritis, papilledema, hereditary optic neuropathies, and multiple sclerosis. [2][3][4][5][6] Until recently most clinical investigations were carried out by using time-domain OCT (TD-OCT), which has been available since the mid 90s on the OCT 1 and since 2002 on the Stratus OCT (both from Carl Zeiss Meditec, Dublin, CA, USA). TD-OCT uses a scanning interferometer and an 820-nm infrared light source that is split into two separate beams: one beam scans a tissue being analysed, and the other one functions as a reference beam that is reflected by a moving reference mirror.…”
Section: Introductionmentioning
confidence: 99%